Local Wisdom Transformation of Custom Society (A Case Study on Banokeling Communities in Banyumas Regency) - Dadan, Sulyana; Priyono, Rawuh Edy; Sulistyoningsih, Endang Dwi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2021)
Modernization and its influences have recently touched various community levels, including communities of custom society and consequently affected the existing local wisdom which has become their life guidance for hundred years. This research aimed at examining the dynamics and transformation of local wisdom existed in the custom society in the middle of modern era development. This research was conducted in Banyumas Regency, precisely on Banokeling custom communities in Pekuncen Village, Jatilawang District. A descriptive-qualitative method was conducted by having in-depth interviews with Banokeling Custom followers and figures as well as Banyumas cultural observers. The research results show that, Banokeling custom communities were highly adaptive to various modernization influences. The local wisdoms were not suddenly disappeared in response to the developing modernization, yet continuously existed with certain adjustments following the recent development. However, there were some forms of local wisdoms which originality was continuously maintained, such as religious identity, clothes, custom houses, and various rituals held routinely. This research concluded that there was local wisdom transformation in Banokeling custom communities, yet the transformation happened in the framework of adaptation with the recent development.